Normalization of a Delay Differential Equation and Bifurcation Leading to an Asymptotically Large Period Cycle - D. V. Glazkov (Моделирование и анализ информационных систем)
We investigate local dynamics of a scalar delay differential equation in the vicinty of the zero solution. When an order parameter is close to the critical value, we use the normal forms method. An asymptotically large period cycle appears as the result of the codimension two bifurcation.